A Almond (Prunus dulcis)Comprehensive overview of cultivars, requirements and fields Management. - Alghamdi, Aisha (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2024)
Almond [Prunus dulcis (Mill.) D.A. Webb, syn. P. amygdalus (L.) Batsch] is located in the Mediterranean countries, and its cultivation is limited to regions with a Mediterranean climate. Almonds are a type of tree nut that is considered a healthy snack and are known for their high protein content, carbohydrates, lipid profile, and antioxidants. It contains flavonoids, vitamin E, riboflavin, amino acids, and the essential minerals manganese, magnesium, copper and phosphorus. Flowering occurs when the requirements for chilling and heat are fully satisfied. When growing self-incompatible cultivars, it is essential to design pollinizers properly. It is recommended to have at least 30% pollinizers to ensure optimal pollination. Almonds can be classified into soft- and hard-shell varieties based on their shell characteristics. Almonds are classified into two categories, sweet and bitter. The weather, including the humidity, temperature, and time of day, heavily influences how much water the almond orchard uses. Nutrition is crucial for the proper development of almonds, regular fruiting, and high-quality yields. Almond propagation through grafting allowed for an improved selection of scions to be clonally propagated. New rootstocks should have the following desirable qualities: tolerance to calcareous and/or other poor soils, ease of multiplication by hardwood cuttings and/or micro-propagation and high vigor. Increased tolerance to heavy and water-saturated soils is becoming an important goal for new hybrids. Clonal propagation is used to capture locally adapted elite genotypes, identifying and propagating hundreds of cultivars in specific production areas. In addition, many molecular studies have been reported that facilitate the transfer of these desirable traits. Generally, this article focuses on managing the fields, from selecting cultivars to harvesting, to achieve high-quality and high-quantity Almond production.